MENINJAU KEMBALI PENYELESAIAN SENGKETA WILAYAH ANTARA THAILAND-KAMBOJA (PEREBUTAN KUIL PREAH VIHEAR) [RETHINKING THE TERRITORIAL DISPUTE SETTLEMENT BETWEEN THAILAND-CAMBODIA (CONQUEST FOR PREAH VIHEAR TEMPLE)] - Jhon Maxwell Yosua Pattinusa (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2021)
International territorial disputes are still one of the most popular security issues today—for example, the conflict in the border area between Thailand and Cambodia. The two countries fought over the Preah Vihear temple, which was considered a national identity related to national pride. For more than 50 years, the two countries have been at loggerheads, and many lives have been caused due to the conflict. Various parties have tried various approaches and efforts to achieve peace. International adjudication through the International Court of Justice made decisions and solutions to answer these problems in 1962. However, until 2011, international adjudication has not succeeded in resolving conflicts/answering international adjudication issues. This paper aims to identify the existing problems using a qualitative approach by focusing on the two main findings, the dynamics of Thailand's attitude towards the results of international adjudication and how these problems were exploited by Thai populism circles, which ultimately led to the 2011 bloodshed. The author sees that this can be avoided if conflict resolution is balanced with public education, namely improving the social environment and strengthening the bottom-up approach to conflict resolution. Absolute peace and conflict resolution can be realized for both countries. Bahasa Indonesia Abstract: Sengketa wilayah internasional masih menjadi salah satu isu keamanan paling populer hingga saat ini. Misalnya saja konflik wilayah perbatasan antara Thailand dan Kamboja. Kedua negara memperebutkan kuil Preah Vihear yang dianggap merupakan identitas bangsa dan berkaitan dengan harga diri bangsa. Selama lebih dari 50 tahun kedua negara bersengketa dan sudah banyak korban jiwa ditimbulkan akibat dari konflik tersebut. Beragam pendekatan serta upaya untuk mencapai perdamaian sudah coba dilakukan oleh berbagai pihak. Ajudikasi internasional melalui International Court of Justice membuat keputusan dan solusi untuk menjawab permasalahan tersebut pada tahun 1962. Tetapi sejak saat itu sampai tahun 2011 silam ajudikasi internasional tidak berhasil meredakan konflik/menjawab permasalahan ajudikasi internasional. Tulisan ini bertujuan untuk mengidentifikasi permasalahan yang ada dengan menggunakan pendekatan kualitatif. Dengan berfokus pada dua temuan utama dinamika sikap Thailand terhadap hasil dari ajudikasi internasional dan bagaimana permasalahan tersebut dimanfaatkan oleh kalangan populisme Thailand yang pada akhirnya menimbulkan pertumpahan darah 2011 silam. Penulis melihat hal ini dapat dihindari apabila resolusi konflik diimbangi dengan pendidikan masyarakat yaitu peningkatan social environtment dan penguatan bottom – up approach pada resolusi konflik, supaya perdamaian dan resolusi konflik yang sesungguhnya dapat terwujud bagi kedua negara.